2020
DOI: 10.1186/s40623-020-01184-4
|View full text |Cite
|
Sign up to set email alerts
|

A case study of correspondence between Pc1 activity and ionospheric irregularities at polar latitudes

Abstract: A possible driver of precipitation of magnetospheric energetic electrons in the high-latitude atmosphere is represented by electromagnetic ion-cyclotron (EMIC) magnetospheric waves. The precipitating particles produce variations, by collision, in the ionized component of the atmosphere, altering its chemistry and electrical conductivity, with a significant impact on the atmospheric processes. In this framework, it would be significant to find experimental evidence of a correspondence between ionospheric electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…One may argue that electron precipitations induced by EMIC waves might ionize neutral particles to modulate ionospheric plasma density (e.g., Francia et al, 2020). However, in general, the resonant electron energy of EMIC waves is high (e.g., Miyoshi et al, 2008), and such electrons typically cause ionization below ~120 km, that is, D region and lower thermosphere and mesosphere (Francia et al, 2020; Turunen et al, 2009, Discussion). Similarly, precipitating protons of >30 keV observed in our Pc1 event (Figure 2) are known to impact ionospheric altitudes of about 110 km (Fang et al, 2007), also far below Swarm.…”
Section: Discussionmentioning
confidence: 99%
“…One may argue that electron precipitations induced by EMIC waves might ionize neutral particles to modulate ionospheric plasma density (e.g., Francia et al, 2020). However, in general, the resonant electron energy of EMIC waves is high (e.g., Miyoshi et al, 2008), and such electrons typically cause ionization below ~120 km, that is, D region and lower thermosphere and mesosphere (Francia et al, 2020; Turunen et al, 2009, Discussion). Similarly, precipitating protons of >30 keV observed in our Pc1 event (Figure 2) are known to impact ionospheric altitudes of about 110 km (Fang et al, 2007), also far below Swarm.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is referred to as ionospheric scintillation (Jiao et al., 2013). In addition to TEC disturbances, ULF waves have also been found to contribute to ionospheric scintillations (Francia et al., 2020; Yizengaw et al., 2018). However, as shown in Figures 3e and 3f, no significant variation in phase sigma index and S4 index (not shown) were observed during the wave activity that occurred during this event, which suggests high‐m ULF waves made little contribution to ionospheric scintillation.…”
Section: Discussionmentioning
confidence: 99%
“…(2015, 2016) reported TEC variations related to Pc4 and Pc5‐6 ULF waves, with the Pc5‐6 waves showing large peak‐to‐peak amplitudes of 2–7 TECU. In addition to VTEC fluctuations, the ionospheric scintillations are also found to be related to Pc1 and Pc5 pulsations (Francia et al., 2020; Yizengaw et al., 2018). Previous studies have shown that the TEC technique is sensitive enough to detect ionospheric response to ULF waves.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of two sensors aligned with magnetic N-S and E-W. The Pc1 geomagnetic pulsations are observed in the 0.1 -1 Hz range, and are used as a proxy for EMIC waves (Paulson et al, 2017;Francia et al, 2020). Three methods were used to analyse the proton aurora H-α spectrum and magnetometer data.…”
Section: Instrumentation and Observationsmentioning
confidence: 99%
“…EMIC waves are typically generated at equatorial latitudes as a result of a fundamental plasma instability (e.g. due to the mixing of hot and cold plasmas) and propagate along field-lines to their foot-points at higher latitudes, where they manifest as structured (see Matsuda et al, 2018) geomagnetic Pc1 (period of 0.2-1Hz; Glaßmeier (2007)) pulsations at the ground (Varlamov et al, 2021;Yahnina et al, 2000;Francia et al, 2020). However, EMIC waves in Svalbard are generally observed as unstructured Pc1 pulsations, suggesting that their origin lies in the outer magnetosphere (Menk et al, 1993;Mursula et al, 1994;Safargaleev et al, 2004;Engebretson et al, 2009;Regi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%